Laparoscopic segment 4 resection including middle hepatic vein with vaginal extraction of the specimen. (March 2020) - Lee, Boram; Choi, YoungRok; Cho, Jai Young; Yoon, Yoo-Seok; Han, Ho-Seong
Highlights: Transvaginal (TV) extraction is an efficacious and minimally morbid techniques. Laparoscopic S4 segmentectomy is a feasible procedure for hepatocellular carcinoma. We performed the TV extraction of the laparoscopic S4 segmentectomy including middle hepatic vein (MHV) specimen.